Citizenship Education and teacher training: Implications for teaching practice - Cardoso, Ana Paula (2021)
Citizenship Education is one of the main challenges faced in educating children and young people in societies undergoing a rapid process of globalization in this decade, and it requires that teachers marshal particular knowledge and skills. Although this is a subject area that is part of the curriculum, it is often undervalued in teaching practice in the 1st cycle of basic education (CEB) [years 1 - 4]. It is, therefore, important to know the degree to which teachers are prepared to address citizenship issues, the relevance they attach to initial and ongoing training in this area, as well as the topics and/or content they would like to see addressed in their ongoing training, with a view to developing competencies related to citizenship in schools. To achieve these objectives, a descriptive cross-sectional study was conducted using a questionnaire survey as an instrument for data collection. The study covered a non-probabilistic sample of 91 mostly female 1st CEB teachers in the municipality of Viseu (Portugal), aged between 35 and 64 years. Regarding the results obtained, the overwhelming majority of teachers never attended training courses related to citizenship education, recognizing that there are aspects of their work that could be improved through attending such course, addressing issues related to teachers’ didactic knowledge and conflict management in the classroom. The suggestions made by the teachers to promote meaningful learning in this area are an important contribution of this research, highlighting the focus on training (teachers and parents/guardians) and in fostering initiatives that promote the involvement of the educational community and other stakeholders in a cooperative and/or collaborative framework. This study aims to raise the scientific community’s awareness of the importance of ongoing training in improvements and innovations in teaching in terms of citizenship education. In particular, the data presented enable policy makers, management bodies and teachers to reflect on the importance and implications that ongoing training has or may have on teaching practice for schools to be able to respond to the changing demands of today’s society.